Respostas
respondido por:
1
Caso seja uma função temos que:
f(x) = x²+8x+16
Igualamos à zero para descobrir as raízes da função.
x²+8x+16 = 0
Por "Bhaskara" temos:
x = -b +/- √Δ / 2a
Caulando Delta...
Δ = b² - 4ac
Δ = (8)² - 4(1)(16)
Δ = 64 - 64
Δ = 0
x =
x' = x'' = -8/2 ⇒ -4
f(x) = x²+8x+16
Igualamos à zero para descobrir as raízes da função.
x²+8x+16 = 0
Por "Bhaskara" temos:
x = -b +/- √Δ / 2a
Caulando Delta...
Δ = b² - 4ac
Δ = (8)² - 4(1)(16)
Δ = 64 - 64
Δ = 0
x =
x' = x'' = -8/2 ⇒ -4
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás